Injury in America : a continuing public health problem (National Academy Press, 1985)
Provides a survey of what is known about injuries, and suggests that there is a vast need to know more. This book traces findings on the epidemiology of injuries, prevention of injuries, injury biomechanics and the prevention of impact injury, treatment, rehabilitation, and administration of injury research.